Comparative analysis of bone health and glycemic control in postmenopausal women: insights from clinical data - Adedeji D. Atere; Ebunoluwa O. Oyewole; Yekeen A. Kosamat; Gregory U. Joseph (Bulletin of Faculty of Physical Therapy)
Abstract Background Menopause leads to significant physiological and biochemical alterations that impact different aspects of health, such as bone mineral metabolism and glycemic control. It is imperative to comprehend these alterations in order to identify potential health hazards and develop preventative measures. This comparative cross-sectional study aimed to evaluate bone-associated markers and glycemic control indices in postmenopausal women (PMP). Methods A sample of 100 women aged 30 years or older was randomly selected and categorized into three groups: PMP (n = 60), premenopausal (PRM) (n = 20), and women in the reproductive age group (RWA) (n = 20). Venous blood samples were collected, and fasting blood glucose (FBG), calcium, phosphorus, uric acid, and alkaline phosphatase (ALP) levels were analyzed using standard laboratory techniques. The insulin and estrogen levels were evaluated using enzyme-linked immunosorbent assay (ELISA), and Homeostasis model assessment of insulin resistance (HOMA-IR), Quantitative insulin sensitivity check index (QUICKI), and Fasting insulin resistance index (FIRI) were calculated. A significance level of p < 0.05 was used in the statistical analysis conducted using SPSS version 25.0. Results The PMP and PRM groups showed significantly greater mean values of FBG, insulin, and HOMA-IR when compared to RWA (p < 0.05), while these groups had lower QUICKI levels. Similar trends were noted for bone-associated markers, with significant differences among the groups (p < 0.05). The correlation results showed that QUICKI had positive correlations with both ALP and phosphorus, while FBG and FIRI had negative connections with both. Conclusion Postmenopausal women demonstrated higher levels of glycemic control indices and bone-related markers compared to premenopausal and reproductive-age women, indicating potential risks for osteoporosis and obesity.